PENGARUH KECERDASAN EMOSIONAL DAN MINAT BELAJAR TERHADAP TINGKAT PEMAHAMAN AKUNTANSI - Fanikmah, Dian Ariami; Kurnia, Kurnia (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2016)
This research is meant to analyze the influence of emotional intelligence and the interest learning of the students to the comprehension level of accounting. This research applies survey method which uses primary data which has been obtained by issuing questionnaires. The population is the students in the last semester in the faculty of Economics in Accounting major at Indonesia School of Economics (STIESIA) Surabaya. The samples are 96 students. The independent variables are emotional intelligence (KE), and interest in learning (MB), meanwhile the dependent variable is the comprehension level of accounting (TPA). The measurement of emotional intelligence consists of self-knowledge aspect, self-control aspect, motivation aspect, empathyandsocialskills aspect. The multiple linear regressions analysis is used as the data analysis technique. The result of the research shows that the emotional intelligence and interest in learning variables have significant influence to the comprehension level of accounting and the interest in learning factor has more dominant influence to the comprehension level of accounting than the emotional intelligence factor.Keywords:Emotional Intelligence, Studentsâ Interest in Learning, Comprehension Level of Accounting